Efektywność międzynarodowych zespołów pracowniczych - Falkiewicz, Maria (The effectiveness of international teams, 2006)
The paper describes and discusses the effectiveness of international teams in the light of different effectiveness, team dynamic, demographic and cultural theories. Above all it presents the role of culture in team dynamic and various factors (cultural, individual, inside team and organizational) which have an impact on the efficiency of an international team. Apart from that it includes the comparison between homogeneous and heterogeneous teams and the results of multinational studies of effectiveness and productiveness.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 24-35